TANC1 methylation as a novel biomarker for the diagnosis of patients with anti-tuberculosis drug-induced liver injury - Dongxue Wu (Nature Portfolio, 2021)
Abstract We aimed to elucidate the differences in genomic methylation patterns between ADLI and non-ADLI patients to identify DNA methylation-based biomarkers. Genome-wide DNA methylation patterns were obtained using Infinium MethylationEPIC (EPIC) BeadChip array to analyze 14 peripheral blood samples (7 ADLI cases, 7 non-ADLI controls). Changes in the mRNA and DNA methylation in the target genes of another 120 peripheral blood samples (60 ADLI cases, 60 non-ADLI controls) were analyzed by real-time polymerase chain reaction and pyrosequencing, respectively. A total of 308 hypermethylated CpG sites and 498 hypomethylated CpG sites were identified. Significantly, hypermethylated CpG sites cg06961147 and cg24666046 in TANC1 associated with ADLI was identified by genome-wide DNA methylation profiling. The mRNA expression of TANC1 was lower in the cases compared to the controls. Pyrosequencing validated these two differentially methylated loci, which was consistent with the results from the EPIC BeadChip array. Receiver operating characteristic analysis indicated that the area under the curve of TANC1 (cg06961147, cg24666046, and their combinations) was 0.812, 0.842, and 0.857, respectively. These results indicate that patients with ADLI have different genomic methylation patterns than patients without ADLI. The hypermethylated differentially methylated site cg06961147 combined with cg24666046 in TANC1 provides evidence for the diagnosis of ADLI.